2006
DOI: 10.1093/jn/136.7.2099s
|View full text |Cite
|
Sign up to set email alerts
|

Pasture Nonstructural Carbohydrates and Equine Laminitis

Abstract: Fresh forages constitute a majority of the diet for many horses and ponies that graze on pastures during the growing season in many parts of the world. Grasses generally predominate in such pastures, with varying proportions of legumes. Nonstructural carbohydrates (NSC) (simple sugars, starch, and fructan) can induce laminitis experimentally, and NSC can accumulate to >400 g/kg of dry matter (DM) in pasture grasses. In this article we discuss the environmental factors affecting NSC accumulation in pastures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
3
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(127 citation statements)
references
References 19 publications
5
115
3
3
Order By: Relevance
“…Moreover, EMS-affected equids seem to be especially prone to development of hoof pain after being allowed to graze pastures at certain times of the year. 24,25 Some have argued that the existence of laminitis should not contribute to the definition for EMS because diagnosis of EMS is intended to predict a risk for laminitis. As is the case for the definition of the human metabolic syndrome, evidence now exists that EMS-affected horses and ponies may be characterized by up-regulated markers of inflammation 26,27 and a propensity to develop arterial hypertension.…”
Section: Defining the Equine Metabolic Syndrome: A Work In Progressmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, EMS-affected equids seem to be especially prone to development of hoof pain after being allowed to graze pastures at certain times of the year. 24,25 Some have argued that the existence of laminitis should not contribute to the definition for EMS because diagnosis of EMS is intended to predict a risk for laminitis. As is the case for the definition of the human metabolic syndrome, evidence now exists that EMS-affected horses and ponies may be characterized by up-regulated markers of inflammation 26,27 and a propensity to develop arterial hypertension.…”
Section: Defining the Equine Metabolic Syndrome: A Work In Progressmentioning
confidence: 99%
“…12 Studies have shown that the NSC content of common pasture grasses tends to increase at certain times of the year (eg, spring, fall) and that development of laminitis is more likely in EMS ponies at these times. 24,62 IR and elevated systemic blood pressure (both components of EMS) are also more prominent when ponies graze high NSC-content pastures. 28 The development of laminitis in equids during pasture grazing should alert veterinarians to the possibility of underlying EMS.…”
Section: Dietary Factors Precipitate and Aggravate Laminitis In Equinmentioning
confidence: 99%
See 3 more Smart Citations